2014
DOI: 10.3390/mi5041469
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characterization of Micromachined Inductive Suspensions Based on 3D Wire-Bonded Microcoils

Abstract: We present a comprehensive experimental investigation of a micromachined inductive suspension (MIS) based on 3D wire-bonded microcoils. A theoretical model has been developed to predict the levitation height of the disc-shaped proof mass (PM), which has good agreement with the experimental results. The 3D MIS consists of two coaxial wire-bonded coils, the inner coil being used for levitation, while the outer coil for the stabilization of the PM. The levitation behavior is mapped with respect to the input param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…As seen from the operation principle of the suspension, the positioning in vertical direction can be performed by changing the coils current and voltage applied to the suspending electrodes "1". Changing the levitation height with the current has been already demonstrated in [4] and [13]- [15]. However, using the electrostatic force generated by electrodes "1", the PM can be held at a desired position while increasing the current value.…”
Section: Resultsmentioning
confidence: 99%
“…As seen from the operation principle of the suspension, the positioning in vertical direction can be performed by changing the coils current and voltage applied to the suspending electrodes "1". Changing the levitation height with the current has been already demonstrated in [4] and [13]- [15]. However, using the electrostatic force generated by electrodes "1", the PM can be held at a desired position while increasing the current value.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of the comprehensive characterization of the ILMA performance in our previous paper [22], namely, a levitation height as a function of the input parameters, i.e., the amplitude and frequency of the excitation currents, as well as the theoretical model to estimate the current versus frequency dependence for a given constant height of the disc shaped proof mass, we showed that the main advantage of using 3D microcoils in the ILMA is the possibility of increasing in the ampere-turn value as a result of an increased number of windings. This increased number of windings can be achieved in a single processing step, as opposed to, for example, the planar coils.…”
Section: Development Of Control Circuitmentioning
confidence: 99%
“…These are related mainly to the range of operating frequencies, which is significantly reduced to a much smaller value for the self-resonant frequency of these 3D structures compared to their 2D counterparts. Due to the reasons above discussed and the results of measurements conducted in [22], the application of 3D microcoils in ILMA requires the following electrical parameters for a voltage suppler, an excitation current, its frequency range, amplitude and waveform, which are summed up below:…”
Section: Development Of Control Circuitmentioning
confidence: 99%
“…Actually, the second circuit can be considered as the current image of the levitation coil. Due to the mentioned particularities of the device, the force interaction along the vertical direction is reduced to an interaction between eddy current i el and the levitation coil current [40]. Considering both the levitation coil and the eddy current circuit as filamentary circles, the mutual inductance between the levitation coil and eddy current can be described by the Maxwell formula ( [41], page 6); thus:…”
Section: The Accelerometer Equation Of Motionmentioning
confidence: 99%